Real-time sound equalizer using component based system / Nazrul Mizuar Anuar - Anuar, Nazrul Mizuar (2007)
The rapid of development of professional audio processing in the market nowadays makes the manufacture ignore the user-requirement perspective. This makes end-user (sound engineers) tries to find a new solution in audio processing. By developing a real-time equalizer software (part of sound processing), the sound engineers may find one of the best solution counter all the problem being faced by sound engineers. These researches are conducted to find the best solution in the development the realtime sound equalizer using all resources that are available in computer hardware and software (component-based system) nowadays. This research had 3 objectives, the first objective is to determined end-user requirement. The specification end-user requirements are gathered through interview, observation and review field study. After gathering the end-user requirement the next objective is to design the real-time sound equalizer application based on requirement capture and data gathered. Than based on the design the researcher develops a prototype real-time sound equalizer by using component based system. This research achieves all the objectives when the final application prototype fiilfills the entire requirement and the design that were being gathered and analyzed.